Fetal growth and activity at 20 to 24 weeks of gestation (preliminary study). - Conde, Ana (2008)
Recent researches show that psychological development begins much before birth and prenatal influences can explain a significant part of the future variability in infants' behaviour and development.The aim of this study was to characterize the fetal development between 20 and 24 weeks of gestation, related to the measures of fetal growth-- iparietal diameter, abdominal circumference, head circumference, femur length and fetal weight-- and fetal activity--fetal heart rate and fetal movements. We also tried to establish if there are any differences in these measures related to the mothers' and fetus' sociodemographic features, obstetrical conditions and exposure to drugs.The sample of this study involved 48 fetus (52.1% female and 47.9% male) with an estimated gestational age (GA) between 20-24 weeks (Mean = 21 weeks and 1 day), whose mothers had appointments at the Obstetric and Gynaecological medical consultation of Júlio Dinis Maternity Hospital (MJD, Oporto). A video tape of the fetal behaviour was made and ultrasound biometry measurements were collected from the morphological ultrasound report.A statistical analysis of fetal data, after gestational age control, showed differences in fetal growth measures related to mothers' occupational status [F(1,41) = 7.28; p = .000], marital status [F(1,41) = 2.61; p = .04], household arrangements [F(1,41) = 2.91; p = .03] and coffee consumption [F(1,40) = 2.55; p = .05]. Differences in fetal activity measures (fetal heart rate) associated to fetus gender [F(1,16) = 5.84; p = .009] were also found.We can conclude about the sensibility of fetal development to prenatal factors related to the mothers' and fetus' sociodemographic features and exposure to drugs.